Aid, ownership, and coordination in the health sector in Ethiopia. Issue 1 (1st January 2018) - Teshome, Shumey B.; Hoebink, Paul
ABSTRACT: The Government of Ethiopia is seen as a owner of its national programs and policies and thus also as a strong coordinator of the foreign aid it receives. This is also the case in the health sector in Ethiopia, where the Ministry of Health have shown leadership in the last two decades. National health plans have been clear-cut and had ambitious objectives, to which the international donor community has adhered. The government-led coordination structures and joint health financing arrangements have been instrumental for improved donor coordination and aid effectiveness in the sector. This has led to impressive results, looking at the poor state of health that the government inherited from former regimes. However, the sector has at once been heavily dependent on foreign sources and characterized by high aid fragmentation. In this paper, we describe the health plans and health financing between 1990 and 2015. We also look at health leadership, donor coordination, and the results of investments in health.